Monitoramento hidrológico e modelagem da drenagem urbana da bacia hidrográfica do Arroio Cancela - Garcia, Joaquin Ignacio Bonnecarrère (2005)
The present work was carried out to evaluate the use of the SWMM model on the Arroio Cancela stream at Santa Maria-RS. The focus was on the calibralibration of the events and understanding parameters involved in the simulation. The hydrologic variables were directly measured and the physical characteristics of the area and the urbanization process determined through GIS techniques. The evaluation of the urbanization process showed a growth of 17% of the urban area and 24% in impermeable area from 1980 to 2004. The increasing in peak flow and runoff volume, in the same period was 109 and 89,9%, respectively. The calibration of the model, for the parameters studies was satisfactory. In a detailed discretisation of the catchment a correlation coefficient of 0,95 was obtained between the observed and predicted values, the mean errors for peak flow and runoff volume were 2,9 and 17,1% respectively. In a simplified discretisation of the catchment, a medium correlation coefficient of 0,94 and medium errors, in the pick flow and drained volume, of 6,3 and 17,3% were obtained. In a sensibility analysis made with detailed discretization of the catchement, the parameters showing higher sensibility were percentage of impermeable area and Manning s roughness coefficient for the modules Runoff and Extran, respectively. In the simulation of the future sceneries of urban expansion, it was possible to evaluate for a extreme condition, an increase in peak flow and runoff volume of 60 and 59%, respectively, in relation to the present situation. These results alert to the need for of a good planning of the land use and occupation of urban areas.